The effect of 5α-oleandrin on keloid fibroblast activities - Dachlan, Ishandono (BMC Proc, 2019)
BACKGROUND: Keloids develop due to hyperactivity of keloid fibroblast (KF) in proliferation, migration, and collagen deposition along with low rates of collagen degradation. These are a result of the Wnt/β catenin signaling pathways under stimulation of TGF-β. 5α-oleandrin can suppress Wnt-targeted genes of osteosarcoma cells. We aimed to evaluate the anti-fibrotic effects of 5α-oleandrin on KF activities. METHODS: We collected the core of keloid materials from six patients who underwent keloid debulking surgery. Passage 4 of KF cells were then treated with mitomycin-C, 5α-oleandrin, and dilution medium as the negative control. To determine the effective dose of 5α-oleandrin, we diluted 5α-oleandrin into various concentrations. The incubation periods were 24 h, 48 h, and 72 h. The anti-proliferation and anti-fibrotic properties were measured using standard assay. RESULTS: Both the mitomycin-C and 5α-oleandrin treated groups indicated decrease in proliferation index (86.16 ± 4.20% and 73.76 ± 4.94%, respectively), collagen deposition index (90.26 ± 1.72% and 71.35 ± 4.26%, respectively), and migration capacity (33.51 ± 1.50% and 28.57 ± 1.58%, respectively). These were significant changes (p ≤ 0.05) compared to the non-treated group. Antifibrotic activities of 5α-oleandrin in cellular proliferation and collagen deposition were better than mitomycin-C. CONCLUSIONS: The 5α-oleandrin has good antifibrotic effect in keloid fibroblast activities.